Consistency and Communication in Committees - Inga Deimen; Felix Ketelaar; Mark T. Le Quement (University of Bonn, Bonn Graduate School of Economics (BGSE), 2013)
This paper analyzes truthtelling incentives in pre-vote communication in heterogeneous committees. We generalize the classical Condorcet jury model by introducing a new informational structure that captures consistency of information. In contrast to the impossibility result shown by Coughlan (2000) for the classical model, full pooling of information followed by sincere voting is an equilibrium outcome of our model for a large set of parameter values implying the possibility of ex post conflict between committee members. Furthermore, abandonning the assumption of sincere voting, we characterize necessary and sufficient conditions for the implementability of the first best decision rule via truthful equilibria.
Keywords: D72; D82; D83; 330; Communication; Committees; Voting